Effect of different nitrogen fixing tree species on soil chemical properties and primary nutrients in lateritic soil - Dalvi, V.V.; Pawar, P.R.; More, S.S.; Shigwan, A.S. (Indian Journal of Agroforestry, 2020)
The study was conducted to know the effect of different nitrogen fixing tree species on soil chemical properties and primary nutrients in lateritic soil. Twenty one year old experiment of nitrogen fixing species was selected for the research. Ten different species viz., T1 (Acacia auriculiformis), T2 (Acacia catechu), T3 (Acacia mangium), T4 (Acacia holosericea), T5 (Albizia lebbeck), T6 (Casuarina equisetifolia), T7 (Pterocarpus marsupium), T8 (Gliricidia sepium), T9 (Dalbergia sissoo), T10 (Cassia siamea) and T11 (Control) were planted in the experiment. During the course of investigation the soil samples were collected at 1m, 2m and 3m distances from the plant and at two depths viz., 0-15 cm and 15-30 cm. The soil was analysed for soil pH, soil electrical conductivity, organic carbon, organic matter, available nitrogen, available phosphorus and available potassium by standard methods. It was revealed that there was no much variation for pH and EC among the ten species. However, some of the NFT species showed higher organic carbon, organic matter, available nitrogen, phosphorous and potassium as compared to control. There were differences in values of above parameters even among NFT species. It was revealed from the study that use of nitrogen fixing trees species showed beneficial effect on available nutrient content in soil and improves organic carbon in soil. NFT species increases nitrogen content in soil and also phosphorous and potassium content showed noticeable increment.